KAJIAN SUBTITUSI AMPAS TAHU DAN PENGGUNAAN NATRIUM BIKARBONAT PADA PEMBUATAN TORTILLA - HP, Sudaryati; Mulyani, Tri; Setiawan, Eka Bagus (UPN VETERAN JAWA TIMUR, 2012)
Tortilla is a similar product in the form of chips or corn chips made from a flattened circular shape with sizes varying thickness. In order to diversify, Tortilla refined products and to enhance the nutritional value. it is necessary to substitute other materials, such as tofu waste flour . The tofu waste flour know still have a very good nutrient composition, especially protein and fiber. But with the substitution of tofu waste flour know can reduce development and crispy Tortilla generated, so the developer needs to add material of which is sodium bicarbonate (NaHCO3). This study aims to determine the effect of substitution and addition of tofu waste flour and sodium bicarbonate (NaHCO3) on the quality of physical, chemical and organoleptic Tortilla. This research used Completely Randomized Design (CRD) which are arranged in factorial which consist of two factors and repeated two times. The substitution factor is the tofu waste flour 10%, 20%, 30% and the addition of NaHCO3 factor II is 0.00%, 0.25%, 0.50%, 0.75%. The best results were obtained on substitution treatment with 10% wheat dregs out with the addition of 0.25% NaHCO3 to produce tortilla with water content of 9.016%, 74.884% starch content, crude fiber content of 2.046%, 7.924% protein content, yield 62.718%, 1.069 crispness kg/cm2, the volume of 20.346% and the development of organoleptic value with a color ranking number 205, 215 flavor, aroma and crispness 204.5 147.